Aligning Interests or Precipitating Energy Transition (Global Journal of Science Frontier Research, 2023)
A lot has been debated about the effects of carbon emissions and their impact climate change Of all the issues that need to be addressed the one that stands out refers to the power sector which absorbs more primary energy than any other sector and accounts for anywhere between a third and half of carbon emissions worldwide
Keywords: paris agreement; climate change; decarbonization; fossil fuels; renewables; regulatory controls; enabling conditions